Robust X‐ray angular correlations for the study of meso‐structures. Issue 3 (8th May 2017) - Lhermitte, Julien R.; Tian, Cheng; Stein, Aaron; Rahman, Atikur; Zhang, Yugang; Wiegart, Lutz; Fluerasu, Andrei; Gang, Oleg; Yager, Kevin G.
Abstract : The theoretical limitations and experimental challenges of X‐ray angular correlation analysis methods are investigated. Using a combination of simulated data and measurements on challenging meso‐cluster samples, prepared using lithography and self‐assembly, the primary experimental challenges are explored. Background scattering, data masking and inter‐object interference are identified as primary challenges. Strategies to overcome correlation artifacts are presented. Abstract : As self‐assembling nanomaterials become more sophisticated, it is becoming increasingly important to measure the structural order of finite‐sized assemblies of nano‐objects. These mesoscale clusters represent an acute challenge to conventional structural probes, owing to the range of implicated size scales (10 nm to several micrometres), the weak scattering signal and the dynamic nature of meso‐clusters in native solution environments. The high X‐ray flux and coherence of modern synchrotrons present an opportunity to extract structural information from these challenging systems, but conventional ensemble X‐ray scattering averages out crucial information about local particle configurations. Conversely, a single meso‐cluster scatters too weakly to recover the full diffraction pattern. Using X‐ray angular cross‐correlation analysis, it is possible to combine multiple noisy measurements to obtain robust structural information. This paper explores the key theoretical limits and experimental challenges that constrain the application of these methods to probing structural order in real nanomaterials. A metric is presented to quantify the signal‐to‐noise ratio of angular correlations, and it is used to identify several experimental artifacts that arise. In particular, it is found that background scattering, data masking and inter‐cluster interference profoundly affect the quality of correlation analyses. A robust workflow is demonstrated for mitigating these effects and extracting reliable angular correlations from realistic experimental data.